2005
DOI: 10.1016/j.ymthe.2004.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 Gene Transfer by Adeno-associated Virus Inhibits MPTP-Induced Nigrostriatal Degeneration in the Mouse Model of Parkinson Disease

Abstract: Mitochondrial dysfunction and oxidative stress have been implicated in Parkinson disease (PD). In addition, genetic evidence points to an important role of protein misfolding, aggregation, and failure in the proteasomal degradation of specific neuronal proteins in the pathogenesis of PD. The chaperone heat-shock protein 70 (Hsp70) reduces protein misfolding and aggregation and protects cells against a variety of adverse conditions, including oxidative stress. Moreover, Hsp70 exerts antiapoptotic activity by bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 62 publications
3
100
3
1
Order By: Relevance
“…That increase was blocked when native DJ-1 was reduced by AS DJ-1. Others have shown that increased Hsp70 can reduce ␣-synuclein protein aggregation and toxicity in Drosophila (41,42), mouse (43,44), and cell culture models (45,46). Hsp70 preferentially binds and stabilizes ␣-synuclein protofibrils, which results in inhibition of larger ␣-synuclein aggregates and cell toxicity (47).…”
Section: Discussionmentioning
confidence: 99%
“…That increase was blocked when native DJ-1 was reduced by AS DJ-1. Others have shown that increased Hsp70 can reduce ␣-synuclein protein aggregation and toxicity in Drosophila (41,42), mouse (43,44), and cell culture models (45,46). Hsp70 preferentially binds and stabilizes ␣-synuclein protofibrils, which results in inhibition of larger ␣-synuclein aggregates and cell toxicity (47).…”
Section: Discussionmentioning
confidence: 99%
“…ER and cellular stress marker proteins such as BiP and Hsp70 have been shown to have elevated expression levels in response to toxic stress in various neurodegenerative disorders, and many reports have detailed the relationship between JNK and Hsp70 (28,29,(33)(34)(35). Mitochondrial protein SOD1 has been implicated in ALS, and its activity is critical against oxidative stress, a hallmark of various neurodegenerative diseases (36).…”
Section: Overexpression Of Sgk1 In Sh-sy5y Cells Regulates 6-ohda-indmentioning
confidence: 99%
“…The neurotoxicity of MPTP depends on the transformation of MPTP to its bioactive form MPP + , which is taken up into dopaminergic (DA) neurons by their DA transporters. MPP + inhibits mitochondrial complex I, leading to decreased ATP production, increased generation of reactive oxygen species, apoptosis, and endoplasmic reticulum stress due to accumulation of unfolded proteins (10,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of Hsp70 has been shown to prevent dopaminergic neuronal loss associated with α-synuclein in Drosophila (9). Hsp70 gene transfer to the dopamine neurons by a recombinant adeno-associated virus also protected the mouse dopaminergic system against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced loss of dopaminergic neurons (10). Moreover, the induction of Hsp70 expression by prior exposure to heat shock offers some protection against 1-methyl, 4-phenyl, pyridinium ion (MPP)-induced neuronal cell death in cultured PC12 cells (11).…”
Section: Introductionmentioning
confidence: 99%